Workshop on the Use of Tiktok Shop in the Start Up Business World with Karang Taruna Dumas - Soelistyowati, Rr Dinar; Hendryansyah, Haldy; Permana, Septian Arief; Saputra, Fajar Ilham; Munggaran, Hauzan Akmal; Ghifar, Ghazy Muhammad; Saputra, Alvin Surya; Setiawan, Turino (Indonesian Journal of Society Development, 2024)
This workshop aims to enable Karang Taruna participants to start businesses by utilizing technology to create jobs and income for Karang Taruna Dumas Bekasi City area activities and provide knowledge to other teenagers around the Duta Harapan and Telaga Mas areas. In the implementation of socialization and workshop activities, it is provided directly using a face-to-face method by the implementing team as well as providing materials and workshop training on related titles. In the implementation, participants are given workshop training with the aim of training and managing their own business in a good and structured manner in order to utilize technology and Internet. Community service activities carried out on Sunday, June 23 2024. This activity was carried out to provide knowledge about how to understand and recognize startups and how to start a business in a well-structured manner